Financing prosperity in the next century - The changing world of banking: Setting the regulatory agenda - James R. Barth; R. Dan Brumbaugh (Levy Economics Institute of Bard College, 1993)
The authors of this brief propose a series of reforms aimed at making bank regulations compatible with the changing financial system. They present evidence to support their contention that change in the market for financial services has reduced the importance of depositories as they have traditionally operated. A dramatic increase in nonbank competition has contributed to a substantial shrinkage in the proportion of total financial assets held by depository institutions. The authors assert that any reforms should take into account the dynamic nature of the financial marketplace. Effective reforms tackling bank regulation must pass a two-part test: they must protect the payments and credit mechanisms in order to promote systemic stability, and they must promote competition within the financial services industry.
Keywords: 330